Transitions in health service use among women with poor mental health: a 7-year follow-up. Issue 2 (22nd June 2022) - Dolja-Gore, Xenia; Loxton, Deborah; D'Este, Catherine; Byles, Julie E
Abstract : Objective: Women suffering from mental health problems require varied needs of mental health service utilisation. Transition between general practitioner and mental health services use are available through the Better Access Scheme initiative, for those in need of treatment. The study's aim was to identify trajectories of mental health service utilisation by Australian women. Design: The Australian Longitudinal Study on Women's Health data linked to the administrative medical claims dataset were used to identify subgroups of women profiled by their mental health service use from 2006 to 2013. Latent growth mixture model is a statistical method to profile subgroups of individuals based on their responses to a set of observed variables allowing for changes over time. Latent class groups were identified, and used to examine predisposing factors associated with patterns of mental health service use change over time. Setting: This study was conducted in Australia. Participants: National representative sample of women of born in 1973–1978, who were aged between 28 and 33 years at the start of our study period. Results: Six latent class trajectories of women's mental health service use were identified over the period 2006–2013. Approximately, one-quarter of the sample were classified as the most recent users, while approximate equal proportions were identified as either early users, late/low user or late-high users. Additional, subgroups were defined as the consistent-reduced user and the late-high users, over time. Only 7.2% of the sample was classified as consistent high users who potentially used the services each year. Conclusion: These findings suggest that use of the Better Access Scheme mental health services through primary care was varied over time and may be tailored to each individual's needs for the treatment of depressive symptoms.